2020
DOI: 10.9734/ijtdh/2020/v41i930322
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Cardiovascular Risk Factors & Their Relative Impact in Diabetic Mellitus-2 Adult Patients’ in Mnazi Mmoja Hospital - Zanzibar

Abstract: Diabetes is characterized by chronic hyperglycemia and disturbances of carbohydrate, lipid and protein metabolism. We aimed to estimate the cardiovascular risk factors and their correlation with type 2 diabetes mellitus (T2DM) in Zanzibar (Mnazi MMoja Hospital) hypothesizing that early detection and treatment of lipid abnormalities can minimize the risk for atherogenic cardiovascular disorders and cerebrovascular accident in patients with T2DM. Methods: The study populations were those patients who prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…These findings are in line with other workers [2,37], who have shown that Many anti-diabetic plants have beneficial effects on the cardiovascular system. Dada et al [10,38], also explained that increased lipid abnormalities are a significant risk factor for cardiovascular complications in type 2 diabetes; hence Lowering LDL-Chol, triglyceride, and raising HDL-Chol has been shown to reduce microvascular disease and mortality in patients with type 2 diabetes. Additionally, According to Murali et al, and Juma et al [10,39] significant control on serum lipids may present hypercholesterolemia's simultaneous coexistence hypertriglyceridemia and also reduce the cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are in line with other workers [2,37], who have shown that Many anti-diabetic plants have beneficial effects on the cardiovascular system. Dada et al [10,38], also explained that increased lipid abnormalities are a significant risk factor for cardiovascular complications in type 2 diabetes; hence Lowering LDL-Chol, triglyceride, and raising HDL-Chol has been shown to reduce microvascular disease and mortality in patients with type 2 diabetes. Additionally, According to Murali et al, and Juma et al [10,39] significant control on serum lipids may present hypercholesterolemia's simultaneous coexistence hypertriglyceridemia and also reduce the cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the introduction of various hypoglycemic agents, diabetes and its complication continue to be a significant problem in the world population [8]. The complication is mainly associated with a risk of atherosclerosis [9,10], coronary heart disease [10,11], stroke, and peripheral vascular diseases [12,13]. Biochemical changes are part of major observable clinical and pathological factors associated with Diabetes mellitus as a derangement in these parameters' levels increase the risk of complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation